SAT0199 An estimate of the proportion of patients with sle receiving off-label treatment with rituximab in european countries. (23rd January 2014) - van Vollenhoven, R.; Seddighzadeh, M.; Jacobsen, S.; Dörner, T.; Ferraccioli, G.; Houssiau, F.; Huizinga, T.; Isenberg, D.; Lászlό, K.; Ruiz-Irastorza, G.; Squatrito, D.; Voskuyl, A.; et al.
Abstract : Background: Rituximab (MabThera; RTX) has not been approved for use in SLE, but uncontrolled observations have suggested efficacy in some patients. There clearly is off-label use of this medication in practice in Europe, but the extent of it has not previously been analyzed. The International Registry for Biologics in SLE (IRBIS), initiated by the SLICC group provided the data for this study. Objectives: To estimate the proportion of SLE patients treated with RTX in Europe. Methods: Data previously submitted to the IRBIS registry by 28 centers in 11 European countries were complemented with additional clinical information from the participating sites and SLE prevalence estimates based on previously published data and data provided by direct contact with participating physicians. For the remaining countries in the European Union (EU) and European Economic Area-European Free Trade Association (EEA-EFTA), estimates were extrapolated on the assumption of regional similarities between countries. Results: Most of the SLE-dedicated rheumatology specialty centers represented in this study had 200 to 300 SLE patients of whom generally <5% were treated with RTX. In the 11 European countries and regions represented in this report the estimated calculated rate of exposure to RTX among SLE patients ranged from 0.6-1.6%. Extrapolating to all 30 EU-EEA-EFTA countries, with an overall population of around 416 million, and with published prevalence estimates for SLE between 3.6 and 7.3 per 10.000 adults, we calculated that between 0.5 and 1.3% of European patients with SLE currently have been treated, off-label, with RTX. Conclusions: In Europe, RTX is estimated to be used off-label in 0.5-1.3% of SLE patients. This modest number suggests that it is chosen only for those patients in whom established therapeutic options have been exhausted. Limitations of the study include the use of extrapolations, and the fact that RTX use by non-rheumatologists was not ascertained. Although controlled evidence for the efficacy of RTX in SLE is lacking, the current usage of RTX in SLE may be considered conservative, given the high medical need in the larger SLE patient population. Supported by a research grant from Roche Disclosure of Interest: None Declared